Parents' Views On Online Learning At Surabaya State University : A Phenomenological Approach - Mawardah, Alfina; Kurniawan, Riza Yonisa; Prakoso, Albrian Fiky (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2025)
The role of parents is very important in supporting motivation, providing facilities, and creating a conducive learning environment at home. The challenges faced include limited internet access, devices, and lack of social interaction and supervision. This study provides an in-depth overview of the dynamics of the role and perceptions of parents in online learning in higher education, and can be a reference for the development of future education policies. This study aims to explore parents' views on distance learning (online) for Economics Education students at Surabaya State University through a phenomenological approach. This study was motivated by changes in the learning system due to the Covid-19 pandemic which encouraged educational institutions to implement online learning as the main alternative. Data collection was carried out through in-depth interviews, observations, and documentation of ten parents of students, and analyzed using NVivo 12 software. The results of the study show that parents' views on online learning vary, influenced by their level of education, experience, and understanding of technology. Some parents view online learning as a flexible solution and still provide learning opportunities, but are also concerned about the effectiveness, interaction, and understanding of the material. Keywords: Parents' views, Distance learning, Students, Challenges, Phenomenology.